802.11 DCF in Dynamic MANET On-demand Routing - Jogendra Kumar (Institute of Advanced Engineering and Science, 2013)
A Mobile Ad-Hoc Network (MANET) is a collection of wireless mobile nodes that communicates with each other without using any existing infrastructure, access point or centralized administration .wireless LAN is an IEEE 802.11 standard supported DCF and MAC features. In this article discuss performance on Distributed Coordination Function (DCF) in Dynamic MANET on demand routing protocols on constant bit rate (CBR).Using Qualnet simulation tools 5.0.2 and finally discuss combine comparative performance analysis 802.11 DCF .The effective performance of 802.11 DCF in Dynamic MANET on demand routing protocol on the performance metrics such as 802.11 DCF: Broadcasts sent, Broadcasts received, Unicasts sent, Unicasts received, CTS packet sent, packet drops due to retransmissions limit, RTS packet sent, ACK packet sent, RTS retransmissions due to time out and packet retransmissions due to ACK timeout..DOI: http://dx.doi.org/10.11591/ij-ict.v2i2.3959